Development of a Synchronous Data Transmission System. - Agomo, Uchenna Udochukwu (Obafemi Awolowo University, 2014)
The development of a 2 - channel synchronous data transmission system is presented. The system is capable of accepting at the input two separate analog voltage signals that have zero to 1 kHz frequency range and amplitude not greater than 2.5 volts. The two analog voltage signals are multiplexed at the input of the-system and converted to corresponding digital representations. These digital representations are then transmitted by means of digital gates from the transmitting section serially and with transmission clock frequency of 6.6 MHz, through cable wire to a remote receiving section, where the received digital representations are re-converted to analog voltage signals and demultiplexed to produce at the output, two separate analog voltage signals plus noise.